2009
DOI: 10.1111/j.1365-2311.2009.01107.x
|View full text |Cite
|
Sign up to set email alerts
|

Crowding and disease: effects of host density on response to infection in a butterfly–parasite interaction

Abstract: Abstract. 1. Hosts experiencing frequent variation in density are thought to benefit from allocating more resources to parasite defence when density is high (‘density‐dependent prophylaxis’). However, high density conditions can increase intra‐specific competition and induce physiological stress, hence increasing host susceptibility to infection (‘crowding‐stress hypothesis’).2. We studied monarch butterflies (Danaus plexippus) and quantified the effects of larval rearing density on susceptibility to the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 65 publications
2
57
4
Order By: Relevance
“…B 282: 20141734 range [22]. Past field and experimental work showed that parasite transmission and host susceptibility increase with monarch larval density [53]. Because winter-breeding sites are distributed along the southern US coast, whereas summer-breeding sites occur farther north, latitudinal differences could confound comparisons of non-migratory versus migratory behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…B 282: 20141734 range [22]. Past field and experimental work showed that parasite transmission and host susceptibility increase with monarch larval density [53]. Because winter-breeding sites are distributed along the southern US coast, whereas summer-breeding sites occur farther north, latitudinal differences could confound comparisons of non-migratory versus migratory behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Because of high mortality during the egg and early larval stages (e.g., Prysby 2004), we followed Lindsey et al (2009) and calculated average larval density per site based on count data for the final three instars (third, fourth, and fifth) only.…”
Section: Citizen Science Data On Parasite Infection and Larval Abundancementioning
confidence: 99%
“…Recently, DDP is considered to have a much broader significance independent of larval conditions, as shown by the labile immune responses to rapidly changing conditions in adult social insect populations (Ruiz-Gonzalez et al 2009). In contrast to DDP, high density conditions may increase intra-specific competition and induce physiological or nutritional stress, increasing host susceptibility to infection and referred to as the crowding-stress hypothesis (Steinhaus 1958;Lindsey et al 2009). …”
Section: Communicated By Biology Editor Dr Ruth Gatesmentioning
confidence: 98%
“…Disease may be a density-dependent factor (Alexander 1974;Møller et al 1993;Moore 2002) due to the greater contact among conspecifics at high densities (Steinhaus 1958) and increased horizontal transmission of viral, bacterial, protozoan and fungal infections May 1979, 1981;McCallum et al 2001). Evidence for densitydependent disease risk is widespread in mammals (Freeland 1979;Hoogland 1979), birds (Brown and Brown 1986;Shields and Crook 1987), insects (Dwyer and Elkinton 1993;Knell et al 1996;Lindsey et al 2009), echinoderms (Lessios 1988;Lafferty 2004) and molluscs (Lafferty and Kuris 1993). As such, organisms that experience high population densities or wide fluctuations in population density would benefit from higher disease resistance; however, immunity is costly to maintain and express (Sheldon and Verhulst 1996;Kraaijeveld and Godfray 1997).…”
Section: Introductionmentioning
confidence: 96%